The Impact of Emotional Intelligence and Learning Independence on Students' Social Studies Activities through Learning Motivation - Lisdayanti; Caska; Gimin (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan UIN Raden Fatah, 2024)
This study aims to examine the effects of emotional intelligence and learning independence on students' learning activities at SMP Negeri in North Tambusai District, Rokan Hulu Regency. The population of this study consisted of 3,037 students, with a sample size of 354 students. Data were collected through questionnaires, interviews, and documentation. Quantitative descriptive analysis and path analysis were employed for data analysis. The results indicate that both emotional intelligence and learning independence significantly influence learning activities by enhancing learning motivation. These findings highlight the importance of considering psychological factors in improving students' motivation and learning activities, offering valuable insights for efforts to enhance the quality of education.